Zakat and Waqf in Supporting the Health Sector: An Analytical Study on the Role of Islamic Financial Instruments in Achieving Sustainable Health Security - Al Zuraib, Mohammd Ali G.; Al-Qahtani, Waleed Khalid (Journal of Neonatal Surgery, 2025)
Zakat and waqf represent two central instruments in the Islamic financial system, with a sustainable solidarity function, particularly in supporting vital sectors such as healthcare. This research aims to study the Shariah and institutional impact of seasonal zakat and health waqf in promoting sustainable health security in Islamic societies. Through a comparative jurisprudential analysis across the four Sunni schools of thought, and employing the framework of Maqasid al-Shariah (higher objectives of Islamic law), the paper explores how Islamic financial tools can bridge funding gaps in health systems and support both preventive and curative medicine within the framework of social justice. The research concludes that expanding the channels of zakat and activating flexible forms of waqf represent an effective approach to achieving public health goals within a renewed Islamic vision